Regulasi Emosi dan Kesadaran Diri pada Masyarakat dalam Menanggapi Bantuan Sosial di Kelurahan Bekasi Jaya : Devi Nanda, Rika Fitriyana - Fitriyana, Rika; Nanda, Devi (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
Since covid-19 pandemic aroused, government has done many things in order to help people survive as the result of this situation. One of the things was cash social donation towards certain people. Of course there’s always pros and cons but in the end it was still distributed through district officer. That is why, the researcher found it’s interesting to look deeper into people’s saelf-awareness and emotion regulation. The purpose of this study was to determine whether there is a relationship between emotion regulation and self-awareness. This study uses a quantitative approach. The subjects in this study were the community in Bekasijaya village as many as 56,462 people with a sample of 140 through a process of characteristic processing. The measuring instrument used is in the form of two scales, namely emotional regulation and self-awareness. The two measuring instruments have been through the validity of the item discriminating power test and the reliability test using Cronbach's alpha which was carried out through the SPSS Version program. The results in this study indicate that there is a relationship between emotional regulation and self-awareness with a correlation coefficient of 0.800** with a significance value of 0.000 (p <0.05). That is, if emotion regulation high, then self-awareness is high, and vice versa, if emotion regulation low, then self-awareness is low.